2016
DOI: 10.1007/s40194-016-0400-2
|View full text |Cite
|
Sign up to set email alerts
|

Allowable stresses in high-frequency mechanical impact (HFMI)-treated joints subjected to variable amplitude loading

Abstract: The effectiveness of high-frequency mechanical impact (HFMI) is considered to rely on the existence of compressive residual stresses. To determine when residual stress relaxation occurs, and what the resulting influence on fatigue improvement is, local stress-strain response in as-welded and HFMI-treated weld toes was modelled under different peak stress conditions. Then, effective notch stress analysis was used to correlate these results with available experimental observations. The simulations showed that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Figures [11][12][13] show that both the investigated fatigue load models underestimate λ HFMI values in many cases, which indicates that the mean stress effect could not be captured using one of these models in general. It is noteworthy that the maximum deviation corresponds to shorter span lengths, as shown in the figures.…”
Section: Comparison With Fatigue Load Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures [11][12][13] show that both the investigated fatigue load models underestimate λ HFMI values in many cases, which indicates that the mean stress effect could not be captured using one of these models in general. It is noteworthy that the maximum deviation corresponds to shorter span lengths, as shown in the figures.…”
Section: Comparison With Fatigue Load Modelsmentioning
confidence: 99%
“…The penalty method provided by the IIW is only applicable for stress ratios of up to 0.52. Nonetheless, several research articles have investigated the effect of HFMI-treatment on the fatigue strength of welded joints subjected to higher R-ratios [5][6][7][8][9][10][11]. An extension of the method proposed in the IIW recommendations was suggested in [7] to cover higher R-ratios, where four reduction classes were proposed for R-ratios greater than 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…So far in the literature, HFMI studies have mainly focused on the degree of improvement in fatigue strength at constant amplitude loading (CAL) [9] [5] [10]. Studies dealing with HFMI material characterization have also been performed in a limited manner including the investigations on highly cold-worked region [11], hardness dependency on steel strength [12], influence of operating parameters [13] and the microstructure after fatigue loading [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary the treatment may decrease the fatigue life at high-applied strains. Based on the numerical simulations, Mikkola et al [17] [9] have shown that full residual stress relaxation may occur at CAL for R = 0.5 and a compressive peak stress of 0.6 f y . Nevertheless, improvement in fatigue strength could be expected even after significant residual stress relaxation due to work hardening and modification of weld to profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation